Mechanochemical treated multi-walled carbon nanotubes for incorporation of metal ions - U. Rinzin (2018)
Ni catalyst was removed from as received multi-walled Carbon Nanotubes (MWNTs) by acid treatment. Then, the nanotubes were treated with 4M HC1 during a ball milling processing yielding mechanochemical treated MWNTs (mech-MWNTs). TEM micrographs indicate that the mech-MWNTs were still of a tubular form but with much shorter length. The equilibrium adsorption of metal ions, e.g Cu2+and Ni2+, on the mech-MWNTs was investigated at room temperature. The adsorption isotherms gave excellent consistence with the Langmuir theory and the best fit values of K-1and Nmaxcan be evaluated using non-linear least-squares. As results, the maximum of Cu2+and Ni2+ions uptake on to the mech-MWNTs are 0.93 ± 0.004 mg/g and 2. 11 ± 0.01 mg/g respectively. There is no evidence indicating that the pore structure and layer surfaces at both ends of the mech-MWNTs are appropriate sites for metal ions adsorption. © 2008 Trans Tech Publications, Switzerland.